2018
DOI: 10.1016/j.ijrefrig.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Modified homogeneous relaxation model for the R744 trans-critical flow in a two-phase ejector

Abstract: Highlights The modified homogeneous relaxation model of the R744 two-phase ejector was proposed. The application range of the proposed model is for a motive nozzle pressure above 59 bar. The proposed model improved the motive nozzle mass flow rate accuracy when compared to the homogeneous equilibrium model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…where: a0 = -1.021449◊10 7 Pa, a1 = 191947.9 Pa/K, a2 = -1484.872 Pa/K 2 , a3 = 6.011561 Pa/K 3 , a4 = -0.01327243 Pa/K 4 , a5 = 1.479618◊10 5 Pa/K 5 and a6 = -6.156445◊10 -9 Pa/K 6 .…”
Section: Model Of Flash Boiling Flow 31 Mixture Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where: a0 = -1.021449◊10 7 Pa, a1 = 191947.9 Pa/K, a2 = -1484.872 Pa/K 2 , a3 = 6.011561 Pa/K 3 , a4 = -0.01327243 Pa/K 4 , a5 = 1.479618◊10 5 Pa/K 5 and a6 = -6.156445◊10 -9 Pa/K 6 .…”
Section: Model Of Flash Boiling Flow 31 Mixture Modelmentioning
confidence: 99%
“…5% lower than those of the HEM. Subsequently, the HRM from [6] was modified by applying the genetic algorithm optimization of the relaxation time correlation by Haida et al [7]. Then the studies on the impact of the relaxation time definition on the CO2 two-phase flow behaviour as well as on the model accuracy were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Gustav Lorentzen (1994) argued that carbon dioxide is the best fluid to replace CFCs and HCFCs. Carbon dioxide is a natural refrigerant with significant advantages such as non-toxicity, nonflammability, zero ozone depletion potential, interesting heat transfer properties, compatibility with usual lubricants, easy accessibility, low cost and high heating capacity (Haida et al, 2018). In the view of increasingly stringent regulations on greenhouse gases, carbon dioxide appeared again as an interesting fluid.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…However, the authors reported that information on temperature, quality and critical flow rate would be required to define a suitable correlation for the relaxation time. More recently, Haida et al [18] have implemented a Homogeneous Relaxation Model (HRM) in ANSYS Fluent. Three different formulation of the HRM relaxation times were confronted with an HEM scheme, including a modified HRM formulation calibrated by means of genetic algorithms.…”
Section: Introductionmentioning
confidence: 99%